Impersonality as reflection of Russian mentality - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is devoted to the some Russian constructions, where the subject is presented as non-controlling the situation, obeying to some irrational force, circumstances. After comparing these meanings with Armenian and English constructions we suppose that impersonality can be considered as the characteristics of Russian linguoculture.
Keywords: Russian language picture, dativ, impersonality, spontaneity, involuntariness